Airway cilia recovery post lung transplantation - Randy Suryadinata; Kovi Levin; Lynda Holsworth; Miranda Paraskeva; Philip Robinson (Immunity, Inflammation and Disease, 2021)
Abstract Background Normally functioning airway cilia is essential for efficient mucociliary clearance to protect the airway from various insults. Impaired clearance may lead to increased risk of infections and progressive lung damage. Significant morbidity in the immediate post lung transplantation period is associated with airway infection, which we hypothesize may be caused by impaired cilia function. Methods Airway cilia beating pattern (CBP) and frequency (CBF) were studied on brushing samples taken from above and below the transplant anastomosis of adult lung transplant recipients (n = 20) during routine bronchoscopies at 6, 12, and 26 weeks posttransplant. Bronchoaveolar Lavage (BAL) samples were also collected at each time points. Results At 6 weeks posttransplant (n = 16), CBP from the donated lung showed reduced beating amplitude with the overall CBF 2.28 Hz slower than the patients' native upper airway cilia (median ± SIQR: 5.36 ± 0.93 Hz vs. 7.64 ± 0.92 Hz, p value < .001). At 12 weeks (n = 16), donor lungs CBP showed recovery with the difference in CBF reduced to 0.74 Hz (6.36 ± 1.46 Hz vs. 7.10 ± 0.86 Hz, p value < .05). Impaired cilia function was not associated with positive BAL cultures. Conclusion Reduced cilia function is evident in the first 12 weeks post lung transplant, with both CBP and CBF returning to levels of function indistinguishable to the patients' upper airway cilia beyond this time.